Sever erythema multiforme post-COVID-19 moderna vaccine: Case report and literature review. (November 2022) - Fadul, Abdalla; Abdalla, El Mustafa; Musa, M.; AL-Mashdali, Abdulrhman; Mudathir Osman, Ahmed EL.; Abdelmahuod, Elabbass
Abstract: Introduction: Although the COVID-19 Vaccine usually causes a few non-serious side effects, serious ones such as Erythema multiforme recently has been linked to it. Case presentation: Our patient presented with severe skin reaction one day post-Covid-19 Moderna vaccine diagnosed as erythema multiforme proven by skin biopsy that responded well to steroids. Discussion: Erythema multiform major, an immune-mediated cutaneous reaction to infections or drugs involving the oral cavity, should be considered a possible adverse effect of numerous vaccinations, including SARSCoV2. Correct patient history gathering enables early detection and successful medical therapy with oral corticosteroids. Furthermore, the disease's rarity makes establishing a causative link difficult. However, because we are still learning about the innovative antiSARSCoV2 vaccines, it is crucial to be cautious of the potential cutaneous adverse responses. Conclusion: Despite being rare, life-threatening adverse reactions can occur post-COVID-19 Vaccination. Highlights: Covid-19 Moderna vaccine is approved for vaccination against CVOID-19 infection. Adverse skin reactions ranging from mild to Sever can occur post-Moderna vaccine. Erythema multiforme Is a rare but serious skin reaction. Moderna vaccine can lead to life-threatening complications in a few selected patients.